Tweeting Along Partisan Lines: Identity-Motivated Elaboration and Presidential Debates. (October 2020) - Jennings, Freddie J.; Bramlett, Josh C.; McKinney, Mitchell S.; Hardy, Molly M.
The influence of partisan identification infiltrates all aspects of a democracy. This study employs an innovative design to explore the presidential debate-viewing experience among young citizens. Data were collected from across the United States for all three 2016 presidential debates between Hillary Clinton and Donald Trump using pretest/posttest surveys and debate viewers' Twitter posts. Examining Twitter expression as a form of political elaboration, the study employs a social identity theoretical perspective to better understand the process through which viewers form political attitudes. Applying the theory of identity-motivated elaboration (TIME) to presidential debates, the current research illuminates how partisan social identification changes the way viewers think about political issues and, resultantly, evaluate candidates and form political opinions. A strong partisan social identification results in greater identity-consistent elaboration and Twitter expression throughout one's presidential debate viewing, which results in more biased candidate image evaluations and, subsequently, stronger preference for the in-party candidate.